Translation Competences for Indonesian Novice Translators - Dewi, Haru Deliana (Journal of Language and Literature, 2019)
Translation competence is a concept that everyone who would like to become a translator should know and understand. Moreover, novice translators or translation students need to achieve all translation competences if they desire to become professional translators. Thus, they must be taught about these translation competences. This paper is the result of a conceptual study, not an empirical one. It explores the literature on translation competences from Translation Studies scholars and adapts them for Indonesian novice translators to learn and achieve. This paper provides explanation, examples, and recommendations for translation students to accomplish translation competences. From the study, 13 translation competences are acquired and those are considered the most suitable with the recent situation of the translation industry in Indonesia. The number of these competences is a not a fixed one as it may decrease or increase in the future following the trends in the translation world.Â Keywords: translation competences, professional translators, novice translators, translation studentsÂ